Regenerative pharmacology for COPD: breathing new life into old lungs - Ng-Blichfeldt,J-P; Gosens,R; Dean,C; Griffiths,M; Hind,M (Thorax, 2019)
Chronic obstructive pulmonary disease (COPD) is a major global health concern with few effective treatments. Widespread destruction of alveolar tissue contributes to impaired gas exchange in severe COPD, and recent radiological evidence suggests that destruction of small airways is a major contributor to increased peripheral airway resistance in disease. This important finding might in part explain the failure of conventional anti-inflammatory treatments to restore lung function even in patients with mild disease. There is a clear need for alternative pharmacological strategies for patients with COPD/emphysema. Proposed regenerative strategies such as cell therapy and tissue engineering are hampered by poor availability of exogenous stem cells, discouraging trial results, and risks and cost associated with surgery. An alternative therapeutic approach is augmentation of lung regeneration and/or repair by biologically active factors, which have potential to be employed on a large scale. In favour of this strategy, the healthy adult lung is known to possess a remarkable endogenous regenerative capacity. Numerous preclinical studies have shown induction of regeneration in animal models of COPD/emphysema. Here, we argue that given the widespread and irreversible nature of COPD, serious consideration of regenerative pharmacology is necessary. However, for this approach to be feasible, a better understanding of the cell-specific molecular control of regeneration, the regenerative potential of the human lung and regenerative competencies of patients with COPD are required.